A solid-free anti-collapse drilling fluid
By adding specific sealing and anti-collapse inhibitors and other additives to the solid-phase drilling fluid, the shortcomings of conventional drilling fluid in terms of sealing and anti-collapse, stability and salt resistance are solved, and the mud layer well wall is achieved. Effective sealing and improved stability of well walls.
Patent Information
- Application Number
- CN202211631378.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-12-19
AI Technical Summary
Conventional solid-phase drilling fluid has the disadvantages of poor sealing and anti-collapse capability, easy leakage, and poor salt resistance, making it difficult to effectively stabilize the well wall and prevent reservoir pollution.
A solid-phase anti-collapse drilling fluid has been developed, including sealing anti-collapse inhibitors, stabilizers, tackifiers, reservoir bridge plugging agents, filter reduction loss agents, lubricants and weighting agents, through the optimization of the formula and Preparation process to improve the anti-collapse, stability and salt resistance of drilling fluid.
The solid-phase anti-collapse drilling fluid can effectively block nano-size pores in the mud strata well wall, inhibit the hydration of clay minerals, stabilize the well wall, prevent collapse, and show good flow under mud shale formation conditions Denature, inhibitory and blocking.
Smart Images

Figure CN116120904B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas field drilling, and in particular to a solid-phase-free anti-collapse drilling fluid. Background Art
[0002] With the development of drilling fluid technology, new requirements have been put forward for the performance of drilling fluid in the drilling of some special wells such as horizontal wells, small hole wells and deep wells. For example: good wellbore purification, maintaining wellbore stability, good wellbore lubrication performance, controlling filtration and leakage, minimizing damage to oil and gas layers, etc. Higher requirements have also been put forward for the environmental protection, stability, pollution, and improvement of mechanical drilling speed of drilling fluid.
[0003] The solid-free drilling fluid system does not contain bentonite, and its main components are organic high molecular polymers and salts. Salts are used as weighting agents and inhibitors to improve the system's ability to prevent collapse; high molecular polymers are used as viscosity and shearing agents to enable the system to have a good ability to carry suspended rock cuttings; compared with clean water, the solid-free drilling fluid can form a thin and tough adsorption film on the well wall, has a certain ability to protect the wall and prevent collapse, and has a good lubrication and drag reduction effect; compared with the solid-phase drilling fluid containing bentonite, it has the advantages of low flow resistance and adjustable viscosity, which is conducive to the normal operation of the downhole motor and the improvement of the rock crushing efficiency of the bottom hole drill bit, thereby maintaining a high drilling speed.
[0004] In view of the shortcomings of conventional solid-free drilling fluids, such as poor plugging and anti-collapse ability, easy leakage, and poor salt resistance, it would be a good choice to prepare a solid-free anti-collapse drilling fluid. Summary of the invention
[0005] In view of the shortcomings of conventional solid-free drilling fluids such as poor sealing and anti-collapse ability, easy leakage, and poor salt resistance, a solid-free anti-collapse drilling fluid suitable for shale formations has been developed to replace conventional drilling fluids to solve problems such as well wall stability and reservoir pollution.
[0006] To achieve the above-mentioned purpose, the technical scheme of the present invention is: a solid-free anti-collapse drilling fluid, comprising: a plugging and anti-collapse inhibitor, a stabilizer, a viscosity-enhancing and shear-enhancing agent, a reservoir bridging agent, a fluid loss reducer, a lubricant, a weighting agent and water, wherein the plugging and anti-collapse inhibitor has a mass of 2-2.5% of the mass of water, the stabilizer PF-ACA has a mass of 0.2-0.4% of the mass of water, the viscosity-enhancing and shear-enhancing agent PF-EZVIS has a mass of 0.3-0.5% of the mass of water, the reservoir bridging agent PF-EZCARB has a mass of 2.5-3.5% of the mass of water, the fluid loss reducer PF-EZFLOHT has a mass of 2-3% of the mass of water, the lubricant PF-LUBEHP has a mass of 2-4% of the mass of water, and the weighting agent HWZJ has a mass of 100%-130% of the mass of water. The plugging and anti-collapse inhibitor is prepared by the following steps:
[0007] First, 1.60g of 4-tert-butylstyrene was added to deionized water and then placed in a reactor. After nitrogen was passed for 20-30min, 1.70g of 3-methyl-2-buteneamine, 1.87g of 4-aminotoluene-3-sulfonic acid, and 0.92g of phenyl ethylenesulfonate were added to the reactor in sequence, and the pH value of the system was adjusted to between 6.5 and 7.5 with a 20%-25% NaOH aqueous solution. The temperature was raised to 60-65°C, and 0.12g of a cross-linking agent N, N-methylenebisacrylamide (MBA) and 0.12g of an initiator ammonium persulfate were added to react for 5-6h. After the reaction was completed, the reaction system was cooled to 20-25°C. The prepared sample was washed with anhydrous ethanol until neutral, and then placed under vacuum drying at 50-60°C. The dried sample was ground to obtain a plugging and anti-collapse inhibitor:
[0008] The beneficial effects of the present invention are as follows:
[0009] The solid-free anti-collapse drilling fluid prepared by the present invention can effectively seal nano-sized pores in the mud shale well wall and inhibit the surface hydration of clay minerals, thereby effectively stabilizing the well wall and preventing collapse, and has good performance in rheology, inhibition and sealing properties under mud shale formation conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is a particle size distribution diagram of the plugging and anti-collapse inhibitor in the embodiment;
[0011] Figure 2 This is a schematic diagram of thermogravimetric analysis of the plugging and anti-collapse inhibitor in the examples. DETAILED DESCRIPTION
[0012] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0013] 1. Example of solid-free anti-collapse drilling fluid
[0014] 1. Preparation of plugging and anti-collapse inhibitor
[0015] First, 1.60g of 4-tert-butylstyrene is added to deionized water, and then placed in a reactor. After nitrogen is passed for 20-30 minutes, 1.70g of 3-methyl-2-buteneamine, 1.87g of 4-aminotoluene-3-sulfonic acid, and 0.92g of phenyl ethylenesulfonate are added to the reactor in sequence, and the pH value of the system is adjusted to between 6.5 and 7.5 with a 20%-25% NaOH aqueous solution. The temperature is raised to 60-65°C, and then 0.12g of a cross-linking agent N,N-methylenebisacrylamide (MBA) and 0.12g of an initiator ammonium persulfate are added to react for 5-6h. After the reaction is completed, the reaction system is cooled to 20-25°C. The prepared sample is washed with anhydrous ethanol to neutrality, and then placed under vacuum drying at 50-60°C. The dried sample is ground to obtain a plugging and anti-collapse inhibitor.
[0016] 2. Preparation of non-solid phase anti-collapse drilling fluid base slurry and optimization of the amount of plugging and anti-collapse inhibitor added
[0017] A solid-free anti-collapse drilling fluid base slurry, wherein the mass of a stabilizer PF-ACA is 0.3% of the mass of water, the mass of a viscosity-enhancing and shear-enhancing agent PF-EZVIS is 0.4% of the mass of water, the mass of a reservoir bridging agent PF-EZCARB is 3.0% of the mass of water, the mass of a fluid loss reducer PF-EZFLOHT is 2.5% of the mass of water, the mass of a lubricant PF-LUBEHP is 3% of the mass of water, and the mass of a weighting agent HWZJ is 106% of the mass of water. Then, the addition amount of the plugging and anti-collapse inhibitor is optimized according to a plugging test, an inhibition evaluation test, and the like.
[0018] In order to determine the amount of the plugging and anti-collapse inhibitor to be added and to further illustrate the effect of the solid-free anti-collapse drilling fluid, the plugging and anti-collapse inhibitor and the solid-free anti-collapse drilling fluid of the examples were subjected to performance tests.
[0019] 2. Performance Test
[0020] 1. Particle size test of plugging and anti-collapse inhibitor
[0021] The particle size of the plugging and anti-collapse inhibitor was tested using a BI-200SM laser scattering instrument produced by Brookhaven Instruments, USA. The particle size test results of the plugging and anti-collapse inhibitor prepared in the embodiment are as follows: Figure 1 The particle size distribution of the plugging and anti-collapse inhibition agent of the present invention is between 50-310 nm, indicating that the plugging agent synthesized by the present invention is of nanometer size, and the plugging agent has a wide distribution range and can effectively plug nanopores of different nanometer sizes.
[0022] 2. Temperature resistance test of plugging and anti-collapse inhibitor
[0023] The plugging and anti-collapse inhibitor was tested at a heating rate of 15°C / min from 30°C to 800°C using a thermogravimetric analyzer (TGA / DSC 1LF, Mettler-Toledo International Ltd., Switzerland), and the initial decomposition temperature of the plugging and anti-collapse inhibitor was 270°C, which proved that the plugging and anti-collapse inhibitor had good temperature resistance.
[0024] 3. Test of drilling fluid rheological properties and water loss wall building performance
[0025] A solid-free anti-collapse drilling fluid base slurry, the formula is: water + 0.3% stabilizer PF-ACA + 0.4% viscosity enhancer and shear enhancer PF-EZVIS + 3.0% reservoir bridge plugging agent PF-EZCARB + 2.5% fluid loss reducer PF-EZFLOHT + 3% lubricant PF-LUBEHP + 110% weighting agent HWZJ, the specific preparation process is as follows:
[0026] Take 5 portions of 400 mL of water, add 12 g of lubricant PF-LUBEHP, 10 g of filtrate reducer PF-EZFLOHT, 12 g of reservoir bridging agent PF-EZCARB, 1.6 g of viscosity enhancer and shear enhancer PF-EZVIS, 1.2 g of stabilizer PF-ACA, and 424 g of weighting agent HWZJ, respectively, and prepare a density of 1.60 g / cm 3 For drilling fluid, each time a substance is added, it needs to be stirred for 15 minutes to obtain 5 parts of base slurry.
[0027] After stirring evenly, 6g, 8g, 10g, and 12g of the plugging and anti-collapse inhibitor prepared in the above manner were added to 4 parts of the base slurry, respectively, to obtain a solid-free anti-collapse drilling fluid containing a plugging and anti-collapse inhibitor addition amount of 1.5%-3%. The drilling fluid prepared in the steps was aged, and the rheology and water loss wall forming properties of the drilling fluid were tested. The results are recorded in Table 1. It can be seen from the results shown in Table 1 that compared with the drilling fluid without plugging and anti-collapse inhibitor, when the plugging and anti-collapse inhibitor was added in the drilling fluid at an amount of 1.5%, 2%, 2.5%, and 3%, the drilling fluid performance was not significantly affected, indicating that the drilling fluid plugging agent has good compatibility. With the increase in the amount of plugging and anti-collapse inhibitor, the apparent viscosity and plastic viscosity of the drilling fluid gradually increase under the same experimental conditions, and the effect on shear force is small. After aging at 150°C for 16 hours, the high-temperature and high-pressure filtration loss of the drilling fluid gradually decreased with the increase of the amount of plugging and anti-collapse inhibition, and the high-temperature and high-pressure filtration loss was the smallest when the amount added was 3%, indicating that the plugging and anti-collapse inhibition has good rheological properties and water loss and wall-building properties, and can effectively reduce the high-temperature and high-pressure filtration loss of the drilling fluid. Even in a high-temperature environment, it can provide good plugging performance, effectively prevent the filtrate from entering the formation, and improve the stability of the well wall.
[0028] Table 1 Drilling fluid rheological properties and filtration performance record
[0029]
[0030]
[0031] Note: The rheological test temperature is 65℃, AV—apparent viscosity, in mPa·s; PV—plastic viscosity, in mPa·s; YP—dynamic shear force, in Pa; API—normal temperature medium pressure filtration loss, in mL; HTHP—high temperature high pressure filtration loss, in mL.
[0032] 4. Drilling fluid plugging performance test
[0033] The selected artificial core was used for CT scanning imaging, the digital core model was established using avizo visualization software, the 3D printing technology was used to construct the 3D printed core, and the 3D printed core was used to simulate the nano-micron fracture formation of the formation. The average flow rate of the drilling fluid system in the 3D printed core was measured, and the Darcy formula was used to calculate the permeability of the 3D printed core before and after adding different mass fractions of plugging and anti-collapse inhibition drilling fluid systems and drilling fluid systems without any plugging agents. The plugging rate of the 3D printed core by plugging and anti-collapse inhibition was calculated to evaluate its plugging performance. Table 2 shows the plugging effect record of plugging and anti-collapse inhibition on the 3D printed core. The plugging rate is (initial permeability-permeability after plugging) / initial permeability×100%. The plugging effects under different plugging and anti-collapse inhibition amounts are shown in Table 2. From the results shown in Table 2, it can be seen that with the increase in the amount of plugging and anti-collapse inhibition, the plugging rate of the core increases, and when the plugging and anti-collapse inhibition is added as the plugging and anti-collapse inhibition, the average plugging rate of the core reaches 83.9%, 85.0%, 85.5%, and 85.6%, which indicates that the plugging and anti-collapse inhibition can effectively plug the nanopores and prevent the drilling fluid from entering the core. At the same time, the optimal amount of plugging and anti-collapse inhibition is 2.5%.
[0034] Table 2 Evaluation of plugging effect under different plugging and anti-collapse inhibition dosage
[0035]
[0036] 5. Drilling fluid inhibition performance test
[0037] A comparison experiment was conducted between 1.5%-3% plugging and anti-collapse inhibition of the solid-free anti-collapse drilling fluid and clean water. The rolling recovery rate was used to evaluate the inhibition performance of the above embodiment. The higher the rolling recovery rate, the better the inhibition performance of the inhibitor. The experimental results are shown in Table 3. From the effect of the inhibitor content on the rolling recovery rate, it can be seen that with the increase in the amount of inhibitor added, the rolling recovery rate increases, and the inhibition performance is better. At the same time, the optimal addition amount of plugging and anti-collapse inhibition is 2%.
[0038] Table 3 Evaluation of plugging effect under different plugging and collapse prevention dosage
[0039] name Recovery rate (%) Shimizu 19.54 Base slurry + 1.5% plugging and anti-collapse inhibition 66.78 Base slurry + 2% plugging and anti-collapse inhibition 72.76 Base slurry + 2.5% plugging and anti-collapse inhibition 74.45 Base slurry + 3% plugging and anti-collapse inhibition 75.39
[0040] 6. Determination of drilling fluid formula
[0041] Combined with the drilling fluid plugging performance test and inhibition performance test, the formula of solid-free anti-collapse drilling fluid is: water + 2-2.5% plugging and anti-collapse inhibitor + 0.2-0.4% stabilizer PF-ACA + 0.3-0.5% viscosity enhancer and shear enhancer PF-EZVIS + 2.5-3.5% reservoir bridging agent PF-EZCARB + 2-3% filtration reducer PF-EZFLOHT + 2-4% lubricant PF-LUBEHP + 100%-130% weighting agent HWZJ.
[0042] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A solid-free anti-collapse drilling fluid, characterized in that: The invention comprises: a plugging and anti-collapse inhibitor, a stabilizer PF-ACA, a viscosity-enhancing and shear-enhancing agent PF-EZVIS, a reservoir bridging agent PF-EZCARB, a fluid loss reducer PF-EZFLOHT, a lubricant PF-LUBEHP, a weighting agent HWJZ and water, wherein the mass of the plugging and anti-collapse inhibitor is 2-2.5% of the mass of water, the mass of the stabilizer PF-ACA is 0.2-0.4% of the mass of water, the mass of the viscosity-enhancing and shear-enhancing agent PF-EZVIS is 0.3-0.5% of the mass of water, the mass of the reservoir bridging agent PF-EZCARB is 2.5-3.5% of the mass of water, the mass of the fluid loss reducer PF-EZFLOHT is 2-3% of the mass of water, the mass of the lubricant PF-LUBEHP is 2-4% of the mass of water, and the mass of the weighting agent HWJZ is 100%-130% of the mass of water; The plugging and anti-collapse inhibitor is prepared by polymerization reaction of 4-tert-butylstyrene, 3-methyl-2-buteneamine, 4-aminotoluene-3-sulfonic acid, phenyl ethylenesulfonate, a crosslinking agent and an initiator; the polymerization reaction comprises the following steps: First, 1.70g of 3-methyl-2-buteneamine is added to deionized water, and then placed in a reactor. After nitrogen is passed for 20-30 minutes, 1.60g of 4-tert-butylstyrene, 1.87g of 4-aminotoluene-3-sulfonic acid, and 0.92g of phenyl ethylenesulfonate are added to the reactor in sequence, and the pH value of the system is adjusted to between 6.5 and 7.5 with a 20%-25% NaOH aqueous solution. The temperature is raised to 60-65°C, and then 0.12g of a cross-linking agent N,N-methylenebisacrylamide and 0.12g of an initiator ammonium persulfate are added to react for 5-6h. After the reaction is completed, the reaction system is cooled to 20-25°C. The prepared sample is washed with anhydrous ethanol to neutrality, and then placed at 50-60°C for vacuum drying. The dried sample is ground to obtain a plugging and anti-collapse inhibitor.
Citation Information
Patent Citations
Strong-inhibition and strong-blockage aluminum-based anti-collapse water-based drilling fluid
CN104650832A
Multi-stage polymer particles having hydrophobically-modified, ionically-soluble stage
CN1047322A